An interdisciplinary approach to improving the diagnosis of vision disorders in children as a priority vector of preventive intervention - Medvedovska, N.V.; Denysiuk, L.I.; Bondarenko, N.Yu; Miroshnikov, O.O. (Suchasna pediatrii︠a︡. Ukraïna, 2024)
The relevance of the study is due to the need to preserve the health of the children's population in the difficult conditions of conducting hostilities on the territory of our country. The modern experience of the developed countries of the world shows the growing spread of ophthalmic pathology, which is recognized as an important problem of modern times. Aim - to substantiate the feasibility of strengthening preventive intervention using an interdisciplinary approach in improving the diagnosis of vision disorders in children of various ages. Materials and methods. The materials for the study were the results of a sociological study of the readiness of educators of secondary educational institutions from all regions of Ukraine (teachers, teachers of schools and lyceums) (a total of 6,215 questionnaires were subject to analysis) and doctors who provide medical and preventive care to children in outpatient polyclinic conditions (of the total analysis 504 questionnaires were submitted). Research methods were: sociological survey, analytical-synthetic, content analysis, system approach and system analysis, medical-statistical. In particular, the latter was used to calculate the representativeness and reliability of the results of planned and conducted sociological research. The results of the study prove the importance of using an interdisciplinary systemic approach in the implementation of modern medical and preventive technologies to improve the diagnosis of vision disorders in children. The development of this direction is a priority, as it allows timely prevention of the influence of controlled risk factors for the formation of visual functions in childhood, which allows increasing the effectiveness of preventive intervention, including due to early diagnosis and correction of detected diseases of the eye and its accessory apparatus in children. A high willingness of secondary school teachers to participate in preventive measures was revealed in combination with an increase in the level of activity of preventive work of medical personnel. The vast majority of respondents expressed the feasibility of introducing regular systematic supervision of vision functions in school-age children (99.40±0.10%) and supporting the implementation of state preventive programs to preserve vision from childhood in Ukraine (97.38±0.20%). Conclusions. The important medico-social significance of disorders of visual functions in children of various ages has an impact on the formation of the health of future generations. The results of the study open the perspective of cross-sectoral interaction with the involvement of educators and doctors in the planning and implementation of comprehensive programs to prevent the development of ophthalmic pathology among children of different ages. The authors declare no conflict of interest.